Effects of the Scientific Argumentation Based Learning Process on Teaching the Unit of Cell Division and Inheritance to Eighth Grade Students - Ceyda Balci; Nilgun Yenice (Journal of Education in Science, Environment and Health)
The aim of this study is to analyse the effects of scientific argumentation based learning process on the eighth grade students’ achievement in the unit of “cell division and inheritance”. It also deals with the effects of this process on their comprehension about the nature of scientific knowledge, their willingness to take part in discussions and their attitude towards the course of science and technology. The study employed the design of pretest-post test matched control group design which is part of semi-experimental design techniques. The participants of the study were 77 students, 38 of whom were in the experiment group and 39 of whom in the control group. The data of the study were collected using four tools: achievement test for the unit of cell division and inheritance, the nature of scientific knowledge scale, argumentation survey and the science and technology course attitude scale. All data collection tools were administered to experiment and control groups as pre- and post test. The data collected were analysed through t- test and ANCOVA (covariance analysis). The findings indicated that academic achievement, comprehension, willingness to discuss and the attitudes towards the course of science and technology of experiment students were significantly better than those of control students at the end of the implementation.